Pemberdayaan Ekonomi Lokal Melalui Pariwisata: Potensi Dan Tantangan Wisata Gedung Merah Putih di Bengkulu - Siti Khodijah; Uswatun Hasanah (Jurnal Aghniya, 2026)
Tourism as a potential sector in empowering the local economy has attracted the attention of many parties, especially in areas that have high cultural and historical value. One place that has great potential to be developed as a tourist destination is the Red and White House in Bengkulu. This building not only holds important historical value for the Indonesian nation, but also has the potential to become a tourist attraction that can have a positive impact on the local economy. This research uses a qualitative approach with the aim of exploring and understanding more deeply the tourism potential of the Red and White House in supporting the economic empowerment of local communities. Through interviews with tourism actors, tourist attraction managers, and local communities, this research analyzes the role of the Red and White House as a local economic resource, as well as the challenges faced in its development. This research also explores how the potential for history-based tourism can create jobs, increase community income, and strengthen local cultural identity. The research results show that although the Red and White House has great potential, there are a number of challenges that need to be overcome, such as lack of promotion, limited infrastructure, and minimal training for managers and the community. With a deep understanding of the potential and challenges, this research offers recommendations for more effective development strategies in maximizing the contribution of Red and White House tourism to empowering the local economy of Bengkulu.